Behind the Burly Q [videorecording (DVD)] - Zemeckis, Leslie Harter; Alda, Alan, 1936-; Evans, Dixie; St. Cyr, Lili, 1917-1999; Storm, Tempest; Hart, Margie, 1913-2000 (First Run Features, 2010)
"Burlesque and vaudeville acts were America's most popular form of live entertainment in the first half of the 20th century, until cinema drove them from the mainstream. To add insult to injury, the art of burlesque became vilified and misunderstood, and was largely left out of our cultural history. By telling the intimate and surprising stories from its golden age through the women (and men!) who lived it, Behind the Burly Q reveals the true story of burlesque, even as it experiences a new renaissance."--Publisher description.